GAMBARAN PENGGUNAAN PESTISIDA OLEH PETANI SAYUR DAN DAMPAKNYA TERHADAP LINGKUNGAN SEKITAR PERTANIAN DI KECAMATAN RASAU JAYA - Sumata, Randi; Rochmawati, Rochmawati; Budiastutik, Indah (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2016)
To increase the toxicity of the plant pests, farmers often use pesticides inappropriately such as excessive doses, overspray frequency, and improper pesticides mixing. These mistakes can cause harmful impacts both forÂ human, and the environment. This study aimed at describing the pesticides use and its environmental effects at farming area in Desa Rasau jaya I, Rasau Jaya District. Using descriptive observation, as many as 34 farmers in Desa Rasau IÂ participated as the samples in this study. The data were collected by conducting interview, observation, and lab test. The instruments used were spectronic 20, observation sheet, and interview guides. The study revealed that there were pesticide residues found in 15 soil samples that exceeded the threshold of 0,01 mg/l. Otherwise, 19 water samples indicated that the pesticide levels were below the threshold of 0,01 mg/l. All farmers used insecticides, 51,5% farmers applied appropriate pesticide dose, 39,4% farmers applied 4 times of spraying from the nursery to the harvest, 100% farmers applied downwind spraying, and 100% farmers did not used PPE. From the findings, the farmers are encouraged to use 1 type of pesticide, apply appropriate dose, apply appropriate spraying frequency (1-2 times a week), and use complete PPE.Key words: pesticides, dose, spraying, water residue, land, farmers, Rasau Jaya, Kubu Raya